Analyticity of a free boundary in one problem of axisymmetric flow - Minenko, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We prove the solvability of a boundary-value problem in the case where the Bernoulli condition is given on a free boundary in the form of an inequality. We establish the analyticity of the free boundary.